WOMEN WORSHIPPING: WORSHIPPING WOMEN IMMANENCE AND TRANSCENDENCE - Sharma, Renuka (Journal of Dharma, 2001)
At the beginning of this new century we are left with vivid images of women in the process of change. Texts from past centuries may give voice to great change if they can be located and interpreted from a womencentered reading. Most spectacular event in recent years concerning women's movements was the fourth women's conference at Haioru, outside Beijing, where around 40 000 women gave homage to the process Of change. The experience of this unique assembly of women remains for many beyond words. Although the programme of meeting in small groups to discuss the political process and personal experiences after the Beijing conference has continued, something ineffable about the experience still remains elusive. In conversations with those present at the conference, I could gather that the impression they had about the conference was something mysterious and awe inspiring. Terms such as connectivity, communitas, presence, speak of another transcendent process not so readily amenable to language. Perhaps it was the circumstances of the conference, held under duress by the Chinese Government, which had not anticipated a womens' NGO conference to be a subversive presence. Thus the political attitude gave rise to methods of surveillance and control by the host government, which inevitably gave rise to subversive strategies of cohesion and organization by the' participant NGO groups, utilizing electronic media, visual media and the best forms networking and activist strength in being together in a civic space for a period of three weeks as an international community in China. Issues that fragment and divide women's communities were suoerseded by the need for collectivity towards survival. The threat of surveillance, abuse and restrictivity by the conference organizers gave rise to a sense unity and cohesion that is seldom seen on such a large scale.